Persepsi Guru SD Terhadap Pelaksanaan Kurikulum 2013 di Kecamatan Kuranji Padang - Ismira, Ismira; Noprina, Winda; Haqqah, Miftahul; Sukandar, Warlan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2021)
The implementation of the 2013 curriculum has generated mixed responses from various groups,especially for those implementing education in schools. There are still teachers who do notunderstand the implementation of the 2013 curriculum. The purpose of this study is to determine theperceptions of elementary school class teachers on the implementation of the 2013 curriculum. Thisstudy uses a quantitative method with a descriptive approach, which is a form of research thatproduces numerical data on data analysis regarding the observed object . The results showed theperceptions of elementary school class teachers in Kuranji District, Padang City on thecomprehension aspect data of 74.72% with good categories, 70.22% acceptance aspects with goodcategories, and 65.20% evaluating aspects with good categories. The average perception ofelementary school class teachers on the implementation of the 2013 curriculum was 70.04% with agood category.